Pengaturan Hukum Perjanjian Kredit Digital dalam Perspektif Hukum Perdata Indonesia: Kajian terhadap Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Muhammad Amir Syarifuddin (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Development of information and communication technology (ICT) has driven innovation in various fields, including the financial sector. One of these innovations is the emergence of digital lending. Digital lending is a loan that is channeled through electronic media, such as the internet, smartphones, or applications. The existence of digital lending has raised various legal issues, one of which is the regulation of digital lending agreements. This is because digital lending agreements have different characteristics from conventional lending agreements. This study aims to examine the legal regulation of digital lending agreements in the perspective of Indonesian civil law. This study uses a normative juridical approach with a library study method. The results of the study show that the legal regulation of digital lending agreements in Indonesia is still inadequate. This is because Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) only generally regulates electronic agreements, including digital lending agreements. To overcome these problems, a more comprehensive legal regulation of digital lending agreements is needed. This regulation can be done through a revision of the ITE Law or through a separate statutory regulation.